(untitled) (Karya Ilmiah Mahasiswa (KIMA), 2022)
This study to analysis the speech acts of da’wah contained in the film Negeri 5 Menara. The research method used is a qualitative descriptive method aimed at describing the forms and functions of speech in the Negeri 5 Menara film. Qualitative research is research that produces data in the form of written or spoken words from speakers and speech partners under study. Therefore, the data collected is in the form of words or utterances. The use of the descriptive method is because the research object can be analyzed by carefully considering linguistic symptoms and as the existence of research reports in the form of data quotations which are described as the results of research analysis. The results of this study indicate that in the film Negeri 5 Menara it is explained in 28 scenes. Every scene in the film depicts various forms of delivering filial da’wah messages to parents, performing prayers, maintaining brotherhood, motivation and studying in the way of Allah SWT.